Screening of soybean (Glycine max L.) genotypes under water stress condition (Bangladesh Journal of Agricultural Research, 2016)
Fifty soybean genotypes were screened for their water stress tolerance in a vinylhouse of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during January to May, 2011. The objective of this study was to screen for drought tolerant soybean genotype(s) for improving yield of soybean under rainfed condition in Bangladesh. Water stress was imposed throughout the growing period by withholding irrigation until appearance of wilting symptom. Water stress caused an overall reduction in seed yield of soybean. However, reduction in seed yield due to water stress varied among the soybean genotypes. Variations were measured by tolerance indices, ranking and cluster analysis. Considering stress tolerance indices, ranking and cluster analysis, the genotypes BARI Soybean 5, BARI Soybean 6, Shohag and BD2331 were found as tolerant to water stress.Bangladesh J. Agril. Res. 41(3): 441-450, September 2016